Beyond Climatic Variation: Human Disturbances Alter the Effectiveness of a Protected Area to Reduce Fires in a Tropical Peatland - Imron, Muhammad Ali; Widyastuti, Kirana; Al Bihad, Dennis; Satria, Ryan Adi; Prayoga, Wiwid; Pradopo, Subyantoro Tri; Suryatmojo, Hatma; Sopha, Bertha Maya; Harrison, Mark E.; Berger, Uta (Frontiers in Forests and Global Change, 2022)
Fire is considered a major threat to biodiversity in many habitats and the occurrence of fire has frequently been used to investigate the effectiveness of protected areas. Yet, despite the known importance of tropical peatlands for biodiversity conservation and serious threat that anthropogenically induced fires pose to this ecosystem, the influence of protected area designation on fire occurrence in tropical peat land has been poorly assessed thus far. Our study addresses this knowledge gap through providing a novel assessment of fire patterns from a tropical peatland protected area and surrounding landscape. We investigated the importance of both climatic factors (top-down mechanism) and human interventions (bottom-up mechanism) on fire occurrence through analyzing 15-years (2001 - 2020) of LANDSAT and MODIS images of the Padang Sugihan Wildlife Reserve and a 10-km buffer area surrounding this in Sumatra, Indonesia. Fire density was assessed in relation to road and canal construction. Monthly and annual precipitation was compared between wet and dry years. The reserve was effective in limiting fire compared to surrounding landscapes only in wet years. We revealed that peat fire occurrence in the protected area and buffer zone was not due to climatic factors alone, with distance from canals and roads also contributing towards fire occurrence. Our results suggest that it is essential to address tropical peatland fire processes at a landscape level, particularly at the surroundings of protected areas, in order to increase the effectiveness of fire protection, improve fire risk classification maps, and conserve threatened tropical peatland wildlife such as the Sumatran elephant.